Gregorčičev "Izgubljeni cvet" kot ljudska pesem - Kumer, Zmaga (Traditiones (Ljubljana), 1999)
When it was sung by folk singers Simon Gregorčič's poem "Izgubljeni cvet" was also recorded on audio tape. Further analysis proves that even when folk singers appropriate a certain literary poem they treat it accordung to the laws of song tradition. This is why poems which had become popular songs represent an indirect proof that folk songs are equivalent to literary prose and that their origin and life cycle do not depend upon it
Keywords: Gregorčič, Simon, 1844-1906; ljudsko slovstvo; oral literature; Slovene literature; slovenska književnost; ljudske pesmi; Ethnopoetics